1996
DOI: 10.1677/jme.0.0170185
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lymphocytes on hormonal secretion by autologous thyrocytes cultured in monolayers

Abstract: We studied the lymphocyte-induced alterations in hormonal metabolism and the production of tumour necrosis factor alpha (TNF-alpha) during coculture of thyrocytes and autologous lymphocytes from 20 patients with Graves' disease and from five normal subjects. Thyroglobulin (Tg) mRNA was assessed by slot-blot analysis under TSH stimulation. Tg, tri-iodothyronine (T3) and cAMP secretion in the presence of TSH were measured by RIA after 3 or 5 days of coculture. TNF-alpha levels produced after 5 days incubation we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 0 publications
3
10
0
Order By: Relevance
“…We also observed that the concentration of FCS did not influence the levels of sICAM-1 which were identical with 10% FCS or 10% NU-serum, a synthetic product containing only 1% serum. These results corroborate those of Ciampolillo et al (1993) who tested only membrane ICAM-1 culture Several reports have been published on human thyrocytes cocultured in monolayers with autologous PBL or ITL lymphocytes (Davies et al 1985, Iwatani et al 1986, Matsunaga et al 1986, Otsubo et al 1988, Sato et al 1993, Massart et al 1995, 1996. However, our present work is the first demonstration of the action of PBL and ITL cocultured with autologous thyrocytes on the expression of membrane and soluble ICAM-1.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We also observed that the concentration of FCS did not influence the levels of sICAM-1 which were identical with 10% FCS or 10% NU-serum, a synthetic product containing only 1% serum. These results corroborate those of Ciampolillo et al (1993) who tested only membrane ICAM-1 culture Several reports have been published on human thyrocytes cocultured in monolayers with autologous PBL or ITL lymphocytes (Davies et al 1985, Iwatani et al 1986, Matsunaga et al 1986, Otsubo et al 1988, Sato et al 1993, Massart et al 1995, 1996. However, our present work is the first demonstration of the action of PBL and ITL cocultured with autologous thyrocytes on the expression of membrane and soluble ICAM-1.…”
Section: Discussionsupporting
confidence: 90%
“…Non-adherent cells were then removed and purified on Lymphoprep as above. Control of the purity of the thyrocyte and lymphocyte populations Thyrocytes Purity of thyroid cells was tested by FCA as previously described (Massart et al 1996). Briefly, phycoerythrin-conjugated CD45 and CD14 mAbs (Immunotech), were used for direct staining of membrane molecules specific for leukocytes and monocytes/macrophages respectively, with murine IgG1 as negative control.…”
Section: Effects Of Cocultures On the Expression Of Icam-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies suggest that increases in endogenous TNFa production may be involved in the regulation of thyroid function in ATD. That is, TNFa and TNFa mRNA are found in human thyroid tissues from patients with Graves' disease and Hashimoto's thyroiditis (1)(2)(3)(4). In FRTL-5 cells, we (5,6) and others (7)(8)(9)(10) have observed that TNFa inhibits type I 5 0 -deiodinase activity and thyroglobulin (Tg), thyroid peroxidase (TPO) and type I 5 0 -deiodinase gene expression.…”
Section: Introductionmentioning
confidence: 92%
“…INTRODUCTION Lymphocytes isolated from peripheral blood (PBLs) from patients with Graves' disease have been shown to have a cytotoxic effect in vitro when cocultured with autologous thyrocyte monolayers whereas intrathyroidal lymphocytes (ITLs) have been found to exert little or no cytotoxicity, depending on the isolation method (Massart et al 1995). We have also demonstrated that the different populations of lymphocytes cultured over thyroid monolayers decrease thyroglobulin (Tg), triiodothyronine (T3) and cAMP production under thyrotrophin (TSH) stimulation (Massart et al 1996). Moreover, we have shown that this inhibition of biochemical and hormonal metabolism in thyroid monolayers is correlated with lymphocyte tumour necrosis factor a (TNF-a) production.…”
mentioning
confidence: 99%